Therapeutic Investigation of Palm Oil Mill Effluent-Derived Beta-Carotene in Streptozotocin-Induced Diabetic Retinopathy via the Regulation of Blood-Retina Barrier Functions - Yamunna Paramaswaran; Aswinprakash Subramanian; Nallupillai Paramakrishnan; Muthusamy Ramesh; Arunachalam Muthuraman (MDPI AG, 2023)
Diabetic retinopathy (DR) primarily progresses into retinal degeneration caused by microvascular dysfunction. The pathophysiology of DR progression is still uncertain. This study investigates the function of beta-carotene (PBC) originating from palm oil mill effluent in the treatment of diabetes in mice. An intraperitoneal injection of streptozotocin (35 mg/kg) was used to induce diabetes, which was then accelerated by an intravitreal (i.vit.) injection of STZ (20 µL on day 7). PBC (50 and 100 mg/kg) and dexamethasone (DEX: 10 mg/kg) were also administered orally (p.o.) for 21 days. At various time intervals, the optomotor response (OMR) and visual-cue function test (VCFT) responses were evaluated. Biomarkers, such as reduced glutathione (GSH), thiobarbituric acid reactive substances (TBARSs), and catalase activity were determined in retinal tissue samples. DR significantly lowers the spatial frequency threshold (SFT) and time spent in the target quadrant (TSTQ), increases the reaching time in the visual-cue platform (RVCP), lowers retinal GSH and catalase activity levels, and elevates TBARS levels. The treatments of PBC and DEX also ameliorate STZ-induced DR alterations. The potential ameliorative activity of PBC in DR is attributed to its anti-diabetic, anti-oxidative, and control of blood-retinal barrier layer properties.